Multi-tier authentication approach for ATMS - Vasanthapriyan, S; Thuseethan, S; U. Wimalasooriya, C (International Journal of Engineering and Technology, 2018)
ATM has become insecure since incredible increase of trendy crimes related to this. Currently, ATM authentication is insecure, use no more than an access card with a PIN for verification. This research looked into the development of a multi-tier authentication approach that inte-grates more than one mechanism in the identity verification process used in ATMs. Recently biometric identification techniques have be-come popular such as facial recognition and fingerprint recognition. It has made significant efforts to rescue the insecure situation at the ATM points. These days Pattern Drawing is also one of the most growing security mechanisms. The combined authentication approach is to serve the purpose both the identification and authentication that card and PIN do in recent years. Proposed plan includes face recognition, fingerprint and pattern drawing together as layers. As far as security concerns proposed approach shows four times better performance than the existing approach in real environments.Â Â
Keywords: ATM; Facial Recognition; Fingerprint Recognition; Pattern Drawing; PIN.